Muscle-sparing skin crease incision posterolateral thoracotomies in pediatric patients: Our experience - Rahul Gupta; Praveen Mathur; Anu Bhandari (Wolters Kluwer Medknow Publications, 2022)
Context: Standard posterolateral muscle cutting thoracotomies in pediatric patients are associated with morbidities in terms of poor motor and esthetic outcomes and also more postoperative analgesia requirement, when compared with muscle-sparing technique. Aims: The aim of this study is to evaluate the outcomes of muscle-sparing skin crease incision posterolateral thoracotomies in pediatric patients in terms of abovementioned variables. Settings and Design: This prospective observational study was conducted over a period from January 2016 to July 2020 in a tertiary care teaching institute. Materials and Methods: All patients of stage 3 empyema and pulmonary hydatidosis were included in the study. Results: Thirty-nine patients fulfilled the inclusion criteria. There were 38 children with organized (Stage 3) empyema and one patient with bilateral lung hydatid. There were 24 males and 15 females; age ranging from 6 months to 15 years. Right thoracotomy was performed in 28, left in 10, and bilateral in one patient with lung hydatid. Adequate exposure was achieved in all cases. Decortication with complete excision of thickened parietal pleura with stripping of the visceral peel and release of the entrapped lung was performed in all 38 patients. In 5 children along with decortication, repair of bronchopleural fistula due to necrotizing pneumonia was performed. Bilateral thoracotomies with pericystectomies were performed with a gap of 3 weeks for lung hydatid. Lung expansion assessment at 3 months was satisfactory. Ultrasound assessment of the latissimus dorsi muscle and serratus anterior muscle at 4 weeks revealed complete integrity in all the cases. Most of the patients achieved satisfactory motor and esthetic outcomes. Conclusions: Muscle-sparing skin crease incision posterolateral thoracotomy is a viable alternative to standard posterolateral muscle cutting thoracotomy, especially in a resource-challenged setting. The technique is easy to perform with satisfactory exposure.